Integrating CLIL for Enhanced Vocabulary Learning - Nikijuluw, Renata Vigeleyn; Tiven, Punggulina Andawaty; Mustamu, Glorya (Program Studi Pendidikan Bahasa Inggris Kabupaten Kepulauan Aru, 2025)
The purpose of this study was to investigate how the CLIL approach improved students' vocabulary. The issue to be answered is whether the CLIL approach has a substantial impact on student vocabulary. The working hypothesis provides a rough solution to this question: using the CLIL technique improves students' vocabulary in a good and meaningful way. The study employed a quasi-experimental design, with a control and an experimental class. Tests were used to collect data, both before and after. Pre-test data were obtained before to the CLIL method's implementation, whereas post-test data were collected following its implementation. Based on the results of the normality and homogeneity tests, the data were declared credible for hypothesis testing. In this study, the differences in vocabulary acquisition between the control and experimental classes were determined using a t-test with a significance level of 0.05. Based on the research findings, many recommendations are made to English instructors, students, and other researchers. English teachers might explore the advantages of adopting CLIL strategies to help pupils improve their vocabulary. Students can also employ CLIL approaches to enhance their vocabulary learning. Other researchers should consider the findings and limitations of this study while studying students at various levels. Classroom action research with the goal of increasing student vocabulary.